PERNIKAHAN USIA DINI DALAM KACA MATA HADIS DAN PSIKOLOGIS - Fauzi Uzy (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2025)
Abstract This article was written using a qualitative method with a library research approach. One of the objectives is to analyze early marriage from a hadith and psychological perspective. The rise of early marriage in modern times raises numerous problems and questions that arise in every discussion among the general public. Both men and women sometimes underestimate the issue of early marriage. They are unaware of and indifferent to the risks involved in their actions once they enter into marriage. They must consider many factors, including the woman's health, the mental readiness of both parties, social factors, and religious beliefs. Although Islam does not specify an age for marriage, there are factors that can negatively impact early marriage if not undertaken with thorough preparation. This can impact psychological, physiological, social, economic, and other factors that can lead to harm. Therefore, it is better to prepare more thoroughly before making a marriage decision, because marriage in Islam is an act of worship and is considered sacred. This research will attempt to uncover in detail the hadith and psychological perspectives on early marriage.